Equity Issues and Stock Price Dynamics. - Lucas, Deborah J; Mcdonald, Robert L (Journal of Finance, 1990)
This paper presents an information-theoretic, infinite-horizon model of the equity issue decision. The model predicts that equity issues on average are preceded by an abnormal positive return on the stock, although for some firms the issue is preceded by a loss; equity issues on average are preceded by an abnormal rise in the market; and the stock price drops at the announcement of an issue. The model provides a measure of the welfare cost of asymmetric information; the welfare loss may be small even if the price drop at issue announcement is large.